The Second Letter to the Corinthians The Pillar New Testament Commentary - Seifrid, Mark A. (Grand Rapids, Michigan : Eerdmans Publishing Company ; Nottingham, England : Apollos, 2014)
The question that Paul set before the ancient church in Corinth -- Do you not recognize that Jesus Christ is in and among you? (2 Cor 13:5) -- remains a critical question for the church today. This commentary by Mark Seifrid seeks to hear Paul's message afresh and communicate it to our time.Seifrid offers a unified reading of 2 Corinthians, which has often been regarded as a composite of excerpts and fragments. He argues that Paul's message is directed at the practical atheism of the Corinthian church -- the hidden heresy that assumes God's saving work in the world may be measured by outward standards of success and achievement.Like all of the Pillar volumes, Seifrid's commentary on 2 Corinthians offers careful grammatical analysis and exegesis with clear pastoral application.
INTRODUCTION -- Before and after Second Corinthians -- Paul's opponents in Corinth and the purpose of Second Corinthians -- The integrity of Second Corinthians -- The theology of Second Corinthians -- COMMENTARY -- The opening of the letter: the call to fellowship with the apostle in Christ (1:1-2:17) -- The body of the letter: the apostolic mission and the apostle in mission (3:1-7:16) -- The closing of the letter: the call to simplicity (8:1-13:14).
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Second Corinthians Commentaries. -- Corinthians Critical Commentary -- Corinthians Criticism and Interpretation; Commentaries; Commentaren (vorm)